The wonder of whitetails - Lantier-Sampon, Patricia, 1952-; Wolpert, Tom. (Milwaukee : Gareth Stevens Pub., 1992)
Text and photographs introduce a North American forest animal, the whitetail deer.
Includes index.
Keywords: White-tailed deer -- Juvenile literature; White-tailed deer; Deer